Literature Riview: Efektivitas Program Holistic Wellness Retreat Garrya Bianti Yogyakarta terhadap Tingkat Stres Pengunjung - Orvala, Naura; Dewi, Alya Anisa; Kurniawati, Indri (CV. Kurnia Grup, 2025)
Increasing public awareness of mental health has encouraged the development of the wellness tourism sector as one of the alternatives to psychological recovery in the modern era. Garrya Bianti Yogyakarta is one of the destinations that offers the Holistic Wellness Retreat program through various activities, such as yoga, meditation, sound healing, floating sound therapy, spa services, and creative wellness activities designed to optimize the well-being of the body and mind. This study aims to evaluate the effectiveness of the program in reducing visitor stress levels. The research uses a descriptive qualitative approach with content analysis of secondary data obtained from Google Review, Garrya Bianti's official website, online media articles, and social media content. The results showed that most visitors experienced increased emotional calmness after participating in the program, which can be seen from the use of terms such as